Design for Manufacture And Assembly Analysis of Baby Stroller - Rahman, M.H.A.; Maidin, N.A.; Ahmad, M.N.; Osman, M.H.; Wahid, M.K.; Ruslan, A.N.M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This paper presents the study design analysis for manufacture and assembly (DFMA) of a baby stroller (Sweet Cherry SCR8 Series) in the aspect of part for manufacturing, assembly process and also handling and insertion difficulties. The problem identified in this study is on the features of the stroller that show a lot of fastener being used and also the usage of both hands in moving the fold latch to fold the stroller. The study has proven to save assembly time by 452.29s which is 23% more efficient than the original design. The number of parts reduced from 179 parts to be 149 parts. The DFA index is also improved from 9.6 to 12.6. The advantages of using DFMA method has been proved in the redesign of the baby stroller. Lastly, the analyzed results are discussed at the end of this research.